2021
DOI: 10.1142/s0218348x21400119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fractal Dimension in Concrete Meso-Structure on Its Axial Mechanical Behavior: A Numerical Case Study

Abstract: The numerical meso-modeling method is a powerful tool for simulating concrete and studying the influence of the geometric form of meso-structure on its mechanical behavior. It is still uncertain regarding how to most effectively characterize the geometric form of the concrete meso-structure and its effect on the observed macro behavior. In this study, the fractal dimension of cement paste was used to describe the geometric form of concrete at the meso-level. A group of meso-models of concrete with various frac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…It is a graph, phenomenon or physical process with self-similar characteristics that can be described by the fractal dimension. There are many methods to calculate the fractal dimension [ 31 , 32 , 33 , 34 ], such as Hausdorff dimension, similarity dimension, box-counting dimension and capacity dimension. In this study, the Hausdorff dimension and box-counting dimension were mainly used for description.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…It is a graph, phenomenon or physical process with self-similar characteristics that can be described by the fractal dimension. There are many methods to calculate the fractal dimension [ 31 , 32 , 33 , 34 ], such as Hausdorff dimension, similarity dimension, box-counting dimension and capacity dimension. In this study, the Hausdorff dimension and box-counting dimension were mainly used for description.…”
Section: Theory and Methodsmentioning
confidence: 99%
“…According to research on fractal theory [22,26,37], it is evident that porous materials like cement and concrete display pronounced fractal characteristics in their internal pore structure, establishing a correlation among T 2 , pore radius r, and fractal dimension D. The subsequent equations can be employed to determine pore sizes larger than r [30,38]:…”
Section: Fractal Theory Based On Nmrmentioning
confidence: 99%
“…Therefore, they concluded that the p D can effectively evaluate the compressive strength. Additionally, Yang [120] explored the relationship between the peak load of concrete, the proportion of coarse and fine aggregates, and the p D . As shown in Figure 13, their findings revealed a robust negative correlation between the p D and compressive strength, demonstrating clear linearity in the curves.…”
Section: Correlation Between Particle Distribution and Compressive St...mentioning
confidence: 99%